Rancang bangun angle pad sebagai alat bantu asah pahat bubut untuk menunjang pembelajaran praktik pemesinan di universitas negeri surabaya - Ramadani, Ali Hasbi; Soeryanto; Cholik, Mochamad; Santoso, Dany Iman; Anwar, Saiful; Prayogo, Aji Catur (Jurnal Teknik Mesin Indonesia, 2024)
In the process of working lathe chisels, students still find it difficult to form tool geometry that is in accordance with standards (chips angle, free angle, and incision angle). Therefore, it is necessary to design an angle pad as a tool to sharpen lathe chisels to support practical learning in the Production Laboratory, Mechanical Engineering Department, Universitas Negeri Surabaya, so that students can understand and be competent in sharpening lathe chisels. The research method used is development, the research method carried out is development research focused on the stages of angle pad design starting from design to function tests and assessments from several experts. The results of this study, in the form of an angle pad that has been tested and has been validated by experts, the results of tests carried out to hone single-cut lathe chisels, the most basic tool angles are rake angle, clearance angle, and cutting edge angle, from the trials carried out produce precise angles on the right flat tool and metric thread tool 600. The validation results from experts related to making angle pads have a value of 93.33 (very decent category).